Case-Based Menu Planner: Web-Based System - Mohd Akhir, Siti Norhanis (Universiti Teknologi PETRONAS, 2008)
Case-Based Menu Planner is a web based system and will apply Case-Based Reasoning (CBR) teclmique. This system is developed in order to help user to know the amount of calories needed in one day and also to give advice to the user about the food they take in one day. Given a user query, the system first retrieves similar cases from the case base in which past successful food menu are stored. Then it formalizes desirability criteria of menu accordance with the user query by using the similar cases. Then the system will gives the solution to the user based on similarity and prompt it as an output. CBR is a problem-solving paradigm that allows us to utilize the specific knowledge of previous problem situation (cases) to solve a new problem situation. New problem solved by finding the most similar past cases and then adapt and reuse them in the new problem situation. The most important concept of CBR is that the ability of continuous learning from experience, since a new problem is retained each time a problem have been solved, making it immediately available for the future problem. The development of this system will focus on entering information or data as a new request and also to retrieve saved case as a result for the problems. The methodology that selected for the system development is Rapid Application Development (RAD). The expected output from the project will be the implementation of real system that can be used by the healthy user which is to know the amount of calories needed by them in their daily life. Besides, the users also can know the amount of calories that contains in their meal and can help the users to plan their intake of calories for each day.